Emotional disclosure as a therapeutic intervention in palliative care: a scoping review protocol. Issue 8 (26th August 2019) - McInnerney, Daisy; Kupeli, Nuriye; Stone, Patrick; Anantapong, Kanthee; Chan, Justin; Candy, Bridget
Abstract : Introduction: Emotional disclosure (ED) is a term used to describe the therapeutic expression of emotion. ED underlies a variety of therapies aimed at improving well-being for various populations, including people with palliative-stage disease and their family carers. Systematic reviews of ED-based psychotherapy have largely focused on expressive writing as a way of generating ED. However, heterogeneity in intervention format and outcome measures has made it difficult to analyse efficacy. There is also debate about the mechanisms proposed to explain the potential effects of ED. We present a scoping review protocol to develop a taxonomy of ED-based interventions to identify and categorise the spectrum of interventions that could be classified under the umbrella term of 'emotional disclosure' in the palliative care setting. By mapping these to associated treatment objectives, outcome measures and explanatory frameworks, the review will inform future efforts to design and evaluate ED-based therapies in this population. Methods and analysis: The review will be guided by Arksey and O'Malley's five-stage scoping review framework and Levac's extension. The following electronic databases will be searched from database inception: CENTRAL, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycINFO, Scopus, Web of Science and MEDLINE. We will include peer-reviewed studies and reviews. We will also check grey literature, including clinical trial registers, conference proceedings and reference lists, as well as contacting researchers. Articles will be screened by at least two independent reviewers and data charted using an extraction form developed for this review. Results will be analysed thematically to create a taxonomy of interventions, outcome measures and theoretical frameworks. Ethics and dissemination: This review does not require ethical approval as it is a secondary analysis of pre-existing, published data. The results will inform future research in the development of ED-based interventions and evaluation of their efficacy in the palliative care setting. We will disseminate findings through peer-reviewed journals.